2017
DOI: 10.3390/s17102278
|View full text |Cite
|
Sign up to set email alerts
|

Application of Negative Curvature Hollow-Core Fiber in an Optical Fiber Sensor Setup for Multiphoton Spectroscopy

Abstract: In this paper, an application of negative curvature hollow core fiber (NCHCF) in an all-fiber, multiphoton fluorescence sensor setup is presented. The dispersion parameter (D) of this fiber does not exceed the value of 5 ps/nm × km across the optical spectrum of (680–750) nm, making it well suited for the purpose of multiphoton excitation of biological fluorophores. Employing 1.5 m of this fiber in a simple, all-fiber sensor setup allows us to perform multiphoton experiments without any dispersion compensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…In Figure 6, the dependence of D(λ ), calculated from Equations (6) and (7), for 7-cell and star structures, is presented. One can observe a good agreement between the D values for both the 7-cell and star structures, with D ranging from 1.5 to 3 ps/(nm × km) in the 700–800 nm region, which is as low as in the case of some previously presented for single-cladding-layer NCHCFs [20,22,30]. These results suggest that both the modeled fibers should be suitable for the purpose of ultrashort laser pulse delivery.…”
Section: Modified Kagomé Hollow Core Fiber—modeling and Optical Prsupporting
confidence: 66%
See 1 more Smart Citation
“…In Figure 6, the dependence of D(λ ), calculated from Equations (6) and (7), for 7-cell and star structures, is presented. One can observe a good agreement between the D values for both the 7-cell and star structures, with D ranging from 1.5 to 3 ps/(nm × km) in the 700–800 nm region, which is as low as in the case of some previously presented for single-cladding-layer NCHCFs [20,22,30]. These results suggest that both the modeled fibers should be suitable for the purpose of ultrashort laser pulse delivery.…”
Section: Modified Kagomé Hollow Core Fiber—modeling and Optical Prsupporting
confidence: 66%
“…All of this interest is well justified when one realizes the potential of the NCHCFs—the overlap of the core mode and cladding area is even lower than in the case of primary (i.e., without the negative-curvature core shape condition) Kagomé fibers, which in turn further reduces any potential absorption and non-linearities of the cladding material, making these fibers ideal candidates for the transmission of ultrashort, high power laser pulses [21,22], as well as making the spectral regions of mid-ultraviolet [23,24] (MUV, 200–300 nm) and near- to mid-infrared (NIR–MIR, 0.8–8 µm) [25,26] available for fiber transmission, without any spectral (due to material absorption) or temporal (due to dispersion) distortions. NCHCFs have also been filled with gases for the purpose of supercontinuum and/or laser light generation [27,28], while recently they have started to appear in the field of biomedical sensing, from multiphoton spectroscopy and microscopy [29,30], to label-free DNA detection [31].…”
Section: Introductionmentioning
confidence: 99%
“…Through a lot of comparison and analysis, it is found that the main factors affecting the performance of HC-PCF include duty cycle, background material, number of cladding layers, core radius and core quartz-ring thickness [ 4 , 17 , 48 ]. The air hole of the HC-PCF mentioned above is circular.…”
Section: Structural Optimization Design Of Hc-pcfmentioning
confidence: 99%
“…Over twenty years have passed since Cregan et al presented the first hollow-core optical fiber (HCF) with a microstructured cladding [1]. Remarkable optical features of HCFs [2][3][4] have resulted in their extensive experimental use, for example in telecommunications [5][6][7], gas and liquid spectroscopy [8][9][10][11][12][13], supercontinuum generation [14,15], high power optical beam delivery [16][17][18], transmission in the spectral regions unavailable for conventional fibers [19][20][21][22], biomedical applications [23,24], and many others. Although the overall scientific reach of both types of HCFs-namely hollow-core photonic bandgap and hollow-core antiresonant optical fibers (HC-PBFs and HC-ARFs, respectively)-has vastly exceeded that of conventional, step index fibers, their full potential is still to be discovered.…”
Section: Introductionmentioning
confidence: 99%